CUFP'13 scribe's report. (2015) - ERIKSEN, MARIUS; SPERBER, MICHAEL; MADHAVAPEDDY, ANIL
Abstract : The Commercial Users of Functional Programming workshop (CUFP) is an annual workshop held in association with the International Conference on Functional Programming (ICFP). The aim of the CUFP workshops is to publicize the use of functional programming in commercial ventures. Its motto is "functional programming as a means, not an end.